Investigation of Biogas Potential (Cattle, Sheep and Goat) for Electricity Generation in Baghlan province - Yousufzai, Mumtaz Ahmad; Aslami, Alyas; Mohsini, Mohammad Shuaib (PT. Riset Press International, 2024)
This study implies to evaluate biogas potential from livestock manure (cattle, sheep and goat) as an alternative to fossil fuel for Baghlan province of Afghanistan. Furthermore, Using biogas to generate electricity. The potential of biogas has been observed as top value with 1107715.3 (m3/ year) in Pul-I-Khumri and as the lowest with 238972.6 (m3/ year) in Tala Wa Barfak for cattle, sheep and goats. when cattle is investigated, the top biogas potential value was 927382.9 (m3/ year) in Khost Wa Fring, then Baghlan Jadeed with 902663.3 (m3/ year) is followed by Pul-I-Khumri with 900555.4 (m3/ year). The highest biogas potential value was 176711.4 (m3/ year) for sheep in Pul-I-Khumri and 45052.0 (m3/ year) for goat in Khost Wa Fring. The study implicates that just three animals (cattle, sheep and goat) generate 12815.6 (Mwh/year) ofeletrical energy with share of 83% cattle, 13% sheep and goat with 5% in the year of 2023. Finally, this paper concludes with a discussion of the environmental, social and economic benefits of biogas production and its potential role in mitigating climate change for this region.